P♤ : A process algebra for modeling prioritized stochastic timed systems (extended abstract) - Domínguez, Martín Ariel (2003)
We present P♤, a Stochastic Process Algebra (SPA) that allows for the modeling of timed systems with priorities and urgency. We de ne the semantics of P♤ in terms of Prioritized Stochastic Automata (PSA), an extension of automata with clock events, priorities and probabilistic symbolic transitions. PSAs are symbolic objects that have a concrete semantics on Probabilistic Timed Transition Systems (PTTS). Therefore, P♤ has semantics in two steps in terms of PTTS. We also de ne several operators directly on PTTS. They include parallel composition and a prioritizing operator. We show that this operators applied to PTTS commute (modulo probabilistic bisimulation) with their relatives in P♤ .